2017
DOI: 10.1051/0004-6361/201730628
|View full text |Cite
|
Sign up to set email alerts
|

The ALMA Frontier Fields Survey

Abstract: Context. The Hubble and Spitzer Space Telescope surveys of the Frontier Fields provide extremely deep images around six massive, strong-lensing clusters of galaxies. The ALMA Frontier Fields survey aims to cover the same fields at 1.1 mm, with maps reaching (unlensed) sensitivities of <70 µJy, in order to explore the properties of background dusty star-forming galaxies. Aims. We report on the multi-wavelength photometric analysis of all 12 significantly detected (>5σ) sources in the first three Frontier Fields… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 73 publications
4
29
0
Order By: Relevance
“…4.5). For example, of the 12 galaxies presented by Laporte et al (2017), with fluxes measured using ALMA at 1.1 mm (González-López et al 2017), seven of them have a size measured by HST F140W/WFC3 similar to the size measured in the ALMA map. On the other hand, for the remaining five galaxies, their sizes are approximately two times more compact 0.6 0.8 1.0 1.2 1.4 1.6…”
Section: Completenessmentioning
confidence: 96%
“…4.5). For example, of the 12 galaxies presented by Laporte et al (2017), with fluxes measured using ALMA at 1.1 mm (González-López et al 2017), seven of them have a size measured by HST F140W/WFC3 similar to the size measured in the ALMA map. On the other hand, for the remaining five galaxies, their sizes are approximately two times more compact 0.6 0.8 1.0 1.2 1.4 1.6…”
Section: Completenessmentioning
confidence: 96%
“…We also compare our measurements of the extended component with the median value of a sample of faint field galaxies in strongly lensed cluster in the Hubble Frontier Fields Survey (González-López et al 2017;Laporte et al 2017). These galaxies at z 1.0-2.9 are detected with Figure 8.…”
Section: What Is the Extended Dust Component?mentioning
confidence: 99%
“…Since we have accurate positions and deep HST imaging, we thus consider available spectroscopic and photometric redshift information. Laporte et al (2017; hereafter Paper II) determine photometric redshifts for all our S /N > 5 detections via SED fitting, finding a mean redshift of z = 1.99 ± 0.27. Five of these high-significance sources (A2744-ID01, A2744-ID02, MACS J0416-ID01, MACS J0416-ID02, and MACS J1149-ID03) have spectroscopic redshifts from the GLASS survey (Treu et al 2015), which are consistent with the photometric redshifts found.…”
Section: Source Redshiftsmentioning
confidence: 99%